2002
DOI: 10.1080/10702890214872
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of National Belonging in Transnational Fields: Ways of Being at Home in Vietnam

Abstract: The notion of transnational citizenship emphasizes the mobility and flexibility of transmigrants with respect to the affective claims and disciplinary operations of the nation-state. Such representations tend to make redundant the analysis of the deep commitments of time, acculturation, and identification that have traditionally been considered the sine qua non of national belonging. I shall aim to put these modalities of citizenship into a more dialectical relation by arguing that in order to reap the full be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 13 publications
0
32
0
2
Order By: Relevance
“…A useful example of this process comes from the work of Ashley Carruthers (2002) who studied the experiences of Australian-born people of Vietnamese descent (labelled as Viet Kieu) who returned to Vietnam for extended periods. Carruthers observed that 'domestic Vietnamese have an extremely finely honed capacity to spot a non-national, who is identifiable by the tiniest departure from locally constituted codes of dress, deportment, speech, and so on ' (2002: 431).…”
Section: The Politics Of Trans/national Belongingmentioning
confidence: 99%
See 1 more Smart Citation
“…A useful example of this process comes from the work of Ashley Carruthers (2002) who studied the experiences of Australian-born people of Vietnamese descent (labelled as Viet Kieu) who returned to Vietnam for extended periods. Carruthers observed that 'domestic Vietnamese have an extremely finely honed capacity to spot a non-national, who is identifiable by the tiniest departure from locally constituted codes of dress, deportment, speech, and so on ' (2002: 431).…”
Section: The Politics Of Trans/national Belongingmentioning
confidence: 99%
“…The pursuit of employment opportunities has been a feature of many studies of 'return mobilities' involving Western-born groups (Carruthers, 2002, Conway & Potter, 2009, Jain, 2013. In these cases, the second generation is not only able to utilise forms of cultural capital, associated with a Western passport and education, but take advantage of the social capital provided by family and kinship ties.…”
Section: Reasons For Returnmentioning
confidence: 99%
“…Cette souplesse a sans doute aidé nos aînés à accepter le fait que le contexte migratoire qui est maintenant le leur les obligeait à modifier certaines pratiques liées à leur identité culturelle (sur la migration de la culture vietnamienne, voir, entre autres, Carruthers 2002et Thomas 1999. Tout en reconnaissant ces modifications (indépendance grandissante des enfants à l'égard de leurs parents, privatisation et simplification des rituels, etc.…”
Section: Resultsunclassified
“…3 The comparative literature shows that return migration may, in some instances, be viewed as the outcome of a failed migration strategy or, conversely, as satisfaction of one's original economic or cultural goals (Cassarino 2004:255). Return migration may enable one to reinvest one's migratory earnings in a place where one has a comparative advantage, or convert them into forms of social or cultural capital that may not be attainable in the migratory destination Carruthers 2002). Some studies emphasise the factors that 'push' migrants to return home: the hardship and stress of life as a migrant; poor health or personal crisis; or the legal, institutional, and cultural obstacles to integration in the migratory destination (Brettell 2000:100).…”
Section: Resultsmentioning
confidence: 99%